2001
DOI: 10.1136/heart.86.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of right ventricular long axis function after atrial repair of transposition of the great arteries

Abstract: Background-While volume derived global indices of right ventricle (RV) function are frequently abnormal after the Mustard procedure, the mechanism for these abnormalities is poorly understood. RV muscle fibres are predominantly arranged longitudinally and thus indices derived in the long axis may better describe RV function. Methods-20 survivors of the Mustard operation were studied (age 7.8-37.3 years, median 14.2 years). Long axis recordings from the apical four chamber view were obtained with the M mode cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…Though we found no difference between groups, TAPSE values in our collective of HLHS patients in general were lower (mean 0.9 cm) than the described normal values for the same age group for the subpulmonary RV (mean 1.9 cm). In 20 patients with atrial switch operation for transposition of the great arteries, Derrick et al found the mean TAPSE of the systemic RV to be 1.2 cm [18] which is similar to that of our cohort. The lower values when compared to subpulmonary RVs could be explained by chronic adjustment of the systemic RV to unnatural loading conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Though we found no difference between groups, TAPSE values in our collective of HLHS patients in general were lower (mean 0.9 cm) than the described normal values for the same age group for the subpulmonary RV (mean 1.9 cm). In 20 patients with atrial switch operation for transposition of the great arteries, Derrick et al found the mean TAPSE of the systemic RV to be 1.2 cm [18] which is similar to that of our cohort. The lower values when compared to subpulmonary RVs could be explained by chronic adjustment of the systemic RV to unnatural loading conditions.…”
Section: Discussionsupporting
confidence: 91%
“…The long-term outcome in terms of functional status and quality of life was reported to be reasonably good in the majority of the patients [4,12,13]. However, there is significant morbidity and mortality associated with specific complications following atrial switch operations, such as systemic ventricular dysfunction [3,14], and baffle complications [3,10]. Reoperations for those late sequelae are demanding, and mortality rate of up to 37% associated to reoperations have been reported [10].…”
Section: Discussionmentioning
confidence: 94%
“…Evidence is increasing that systemic ventricles that are not of left ventricle morphology respond differently to medical interventions. [26][27][28][29] No significant benefit could be detected in young adults with systemic right ventricles who were treated with angiotensinconverting enzyme inhibitors or angiotensin receptor blockers, 30,31 leading to speculation that vasodilators might be poorly tolerated in a circulation with intrinsically limited ventricular filling. 32 The high level of placebo response we observed, as well as the interaction between systemic ventricular anatomy and the primary outcome, are important considerations for the design of future clinical trials.…”
Section: Commentmentioning
confidence: 99%